Phosphodiesterase 5 (PDE5) restricts intracellular cGMP accumulation during enterotoxigenic Escherichia coli infection. Issue 1 (9th November 2020) - Foulke-Abel, Jennifer; Yu, Huimin; Sunuwar, Laxmi; Lin, Ruxian; Fleckenstein, James M.; Kaper, James B.; Donowitz, Mark
ABSTRACT: Diarrhea caused by enterotoxigenic Escherichia coli (ETEC) has a continuing impact on residents and travelers in underdeveloped countries. Both heat-labile (LT) and heat-stable (ST) enterotoxins contribute to pathophysiology via induction of cyclic nucleotide synthesis, and previous investigations focused on intracellular signal transduction rather than possible intercellular second messenger signaling. We modeled ETEC infection in human jejunal enteroid/organoid monolayers (HEM) and evaluated cyclic nucleotide pools, finding that intracellular cAMP was significantly increased but also underwent apical export, whereas cGMP was minimally retained intracellularly and predominantly effluxed into the basolateral space. LT and virulence factors including EatA, EtpA, and CfaE promoted ST release and enhanced ST-stimulated cGMP production. Intracellular cGMP was regulated by MK-571-sensitive export in addition to degradation by phosphodiesterase 5. HEMs had limited ST-induced intracellular cGMP accumulation compared to T84 or Caco-2 models. Cyclic nucleotide export/degradation demonstrates additional complexity in the mechanism of ETEC infection and may redirect understanding of diarrheal onset.